2022
DOI: 10.3390/jfb13020077
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide (GO) Materials—Applications and Toxicity on Living Organisms and Environment

Abstract: Graphene-based materials have attracted much attention due to their fascinating properties such as hydrophilicity, high dispersion in aqueous media, robust size, high biocompatibility, and surface functionalization ability due to the presence of functional groups and interactions with biomolecules such as proteins and nucleic acid. Modified methods were developed for safe, direct, inexpensive, and eco-friendly synthesis. However, toxicity to the environment and animal health has been reported, raising concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(34 citation statements)
references
References 137 publications
1
33
0
Order By: Relevance
“…Graphene and GO nanomaterials present unique chemical and electrical features, which have highlighted them as promising materials to improve signal responses in novel sensing technologies such as electrochemical biosensors, fluorescence resonance energy biosensors transfer (FRET), laser desorption/ionization mass spectrometry (LDI-MS), and surface-enhanced Raman spectroscopy (SERS) (Chauhan et al, 2017;Janegitz et al, 2017;Morales-Narváez et al, 2017). GO possesses a hydrophobic domain structure and hydrophilic oxygen-containing functional groups, which provide good biocompatibility and water dispersibility (Ghulam et al, 2022). However, their features, including high surface area and a high affinity for a variety of biomolecules (antibodies, enzymes, DNA, cells, and proteins), have made them ideal for next-generation biosensors (Lee et al, 2016).…”
Section: A Brief Look At Nanomaterials Incorporated Into Sensorsmentioning
confidence: 99%
“…Graphene and GO nanomaterials present unique chemical and electrical features, which have highlighted them as promising materials to improve signal responses in novel sensing technologies such as electrochemical biosensors, fluorescence resonance energy biosensors transfer (FRET), laser desorption/ionization mass spectrometry (LDI-MS), and surface-enhanced Raman spectroscopy (SERS) (Chauhan et al, 2017;Janegitz et al, 2017;Morales-Narváez et al, 2017). GO possesses a hydrophobic domain structure and hydrophilic oxygen-containing functional groups, which provide good biocompatibility and water dispersibility (Ghulam et al, 2022). However, their features, including high surface area and a high affinity for a variety of biomolecules (antibodies, enzymes, DNA, cells, and proteins), have made them ideal for next-generation biosensors (Lee et al, 2016).…”
Section: A Brief Look At Nanomaterials Incorporated Into Sensorsmentioning
confidence: 99%
“…Thus, a comprehensive analysis is required to know the possible long- and short-term effects of AgNP-related materials before its full-scale application in veterinary and animal sciences ( Ema et al, 2017a ; Yuan et al, 2021 ). A number of previous studies were conducted to evaluate possible mechanisms of graphene oxide or AgNPs-induced toxicity with various kinds of cells lines and animal models ( Liao et al, 2019 ; Ghulam et al, 2022 ). Numerous studies have also shown the toxicological effects of graphene oxide-silver nanoparticle nanocomposites (GO-AgNPs) on human cells and animal ( Ali et al, 2018 ; Courtois et al, 2019 ; Yuan et al, 2021 ), which even remains two generations post-maternal exposure ( Ellis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, mostly metallic (e.g., gold and iron oxide) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] or carbon-based (e.g., carbon black, reduced graphene oxide and graphene quantum dots) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] NPs have been used for the photoporation of cells. However, concerns regarding the potentially toxic effects of such essentially non-degradable nanoparticles [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ] have led researchers to seek more biocompatible alternatives, such as polydopamine NPs (PDNPs). PDNPs possess excellent photothermal properties across the visible range of wavelengths [ 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%